Self-reported sick leave following a brief preventive intervention on work-related stress. (20th October 2021) - Hultén, A-M; Bjerkeli, P; Holmgren, K
Abstract: Background: General practitioners (GPs) play an important role for early identification and prevention of sick leave among patients perceiving ill health due to work-relates stress. In order to fulfil the role, they need adequate methodologies and tools. This study aimed to evaluate the effectiveness of a brief intervention in primary health care including early identification of work-related stress combined with feedback at consultation on the number of self-reported sick leave days. Methods: A randomised controlled trial was performed at seven primary health care centres in western Sweden. Self-reported sick leave data collected between November 2015 and January 2017 were analysed prospectively. The study included 271 employed, non-sick-listed patients aged 18-64 years seeking care for mental and/or physical health complaints. The intervention group received a brief intervention about work-related stress, including training for GPs, screening of patients' work-related stress, feedback to patients on screening results and discussion of measures at GP consultation. The control group received treatment as usual. Results: At 6-month follow-up 59/105 (56%) in the intervention group and 61/115 (53%) in the control group reported no sick leave. At 12-month follow-up the corresponding numbers were 61/119 (51%) and 57/122 (47%) respectively. There were no statistically significant differences between the intervention group and the control group in the median number of self-reported sick leave days. Conclusions: The brief intervention showed no effect on the numbers of self-reported sick leave days. However, using sick leave as an outcome measure was difficult, as sick leave is multifactorial and the data has a non-normal distribution. In addition, sick leave might be used as an indicator as well as a possible treatment of ill health. Other actions and interventions to address patients perceiving ill health due to work-related stress should be explored. Key messages: Sick leave is used as an indicator and as a treatment of ill health, which can complicate the evaluation of studies. The complexity of primary health care trials calls for other evaluation methods.